Voltage Stability Improvement Using the 21st Centur y Power Transformer - Mwaniki, Charles (Innovative Systems Design and Engineering, 2012)
The 21st Century Power Transformer is produced by combining modern high voltage cross-linked polyethylene (XLPE) cable technology with conventional transformer. The technique of solid insulation is adopted in the new dry transformer so that the pollution from leakage of insulating oil can be avoided, and so XLPE cable-winding transformer is very suitable in environment sensitive places such as populous cities, hydropower stations, and underground caver and so on. This paper is meant to show that the marriage of the well-proven high voltage power cable technology with transformer technology sets a new standard in improving power system voltage stability.
Keywords: voltage stability; Voltage collapse; Dryformer; Load flow; Transformer parameters